(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
This essay aims to chart the chronological trajectory of the boria in order to show how it had evolved from a ritualistic theatre to become Penang's unique Malay-Muslim cultural heritage. In achieving this aim, the essay traces boria's etymology, its origin and the socio-historical factors that have moulded it into a ritualistic form of theatre. The essay then discusses the features of the boria that help to provide it a specific Malay-Muslim identity by exploring factors such as the language of the comic sketches and songs, the transmission of cultural, religious and Malay political values via the boria performance. The essay concludes by discussing the factors that have threatened this cultural heritage with extinction and measures that have been taken to revive it.